PEKERJAAN EARTHWORK DENGAN PENERAPAN METODE M-PERT DI AREA KAWASAN INDUSTRI - Sugeng Rahardjo (Institut Teknologi Sepuluh Nopember, 2019)
Earthwork Work with the Application of the PERT-Method in the Industrial Estate area. At the present time the need for industrial area in Jakarta and its surrounding areas is much higher than its availability. The average delay in earthwork is 6.1% white the weight of earthwork work in a construction project reacted 13.48%.In order to overcome the delay in implementation time, researchers used the M-PERT method can increase the accuracy of implementation time by 99%, The processing The results of the statistical analysis obtained the influential factors in earthwork work on industrial areas based on the M-PERT method whice are: exavator selection, similarities in the network, combining activities, understanding PERT activities, manual calculation, recalculating PERT, increasing crashing time, identification of cut & fill and effects duration of activity. Based on the validation results on the ripening work of the G1 plots in the industrial zone of Krakatau II Cilegon Banten, the application of M-PERT method, the result is 72 , 55 days, whice produced the error rate of 1.99%.